A implantação da manutenção centrada na confiabilidade no setor de pultrusão na indústria de compósitos - Cunha, Leonardo Augusto da (2023)
The pultrusion process is the most automated process and with the least human interference in the manufacture of composites. And, like any existing process, it is subject to failures, which can result in a huge loss of productivity, as it is a continuous process, in addition to the risk of generating a large number of defective products. The risks increase even more when the machines do not have a defined maintenance plan, in addition to not having an automated and standardized data collection. There are some approaches that can help to overcome this situation, such as the implementation of sensors and programmable controllers for data collection, carrying out more specific training, writing a maintenance manual, implementing a new maintenance policy in the company, among others. With that in mind, it is believed that maintenance focused on reliability can bring positive results for the company, without having a high investment with the acquisition of new assets for monitoring and data control, and without having a drastic change in the existing maintenance policy in the company. It is a methodology that seeks to identify the most critical maintenance tasks and schedule them based on data and information about the reliability of the equipment. For this, access to machine data was acquired, as well as to the maintenance history. This analysis was performed with the help of Python programming, which allowed the identification of information that was not só evident. The implementation of this methodology not only has the purpose of comparing costs, but also to demonstrate in the best possible way, point by point, how the application of this technique should be approached and executed effectively in practice, proposing a new complete maintenance plan.